Plan de mejoramiento de la productora de televisión Masmedios Producciones S.A.S, ubicada en la ciudad de Manizales, Caldas (2015)
Improvement plan for the company Masmedios Productions SAS focused on correcting the flaws that has been showing in order to increase productivity and national expansion, as the company is competing with companies involved in television production industry. To develop the plan will be based on management by objectives AOP for setting goals, looking to the subordinates and superiors establish performance goals, review the scope and allocate rewards, achieving the main objective of the plan identify critical points through the application of an exploratory study through observation and survey. As a result of the plan they were obtained that the company lacks the staff and the organization necessary for the proper execution of processes and thus slows the productivity of the same, leading to conclusions implementing a schedule with a series of strategies in order to make continuous and effective monitoring, which includes as an essential part for such improvement, recruitment and creation of an organization by section to allow the organization running processes, also making an analysis of the investment required for this finding feasible effectiveness. It is important that the manual process is treated and handled with the development and growth of the media as a business, you should always run a monthly process of all areas of the company and thus for subsequent occasions does not require an improvement plan as long to make changes and many improvements.